The concept of negotiation from the Islam perspective (in the Islamic organization) - Ramdani, Abbas; Mohammed, Rosli; Ahmad, Mohd Khairie (Medwell Journal, 2016)
The discussion of the negotiation process and outcome concept has been largely discussed based on different perspectives that informed by its value system.Meanwhile, what has remained unexplored is the possibility of another approach which is the Islamic perspective, giving rise to similar concepts of negotiation in practice. The dearth of literature on negotiation from Islamic approach can be seen to be has caused lack of attention which is assumed lead to lack of understanding of the issue among the Islamic organization. Therefore, the purpose of this paper is to identify the concept of negotiation from the Islamic perspective.A series of interviews were conducted to drive data from Informants of this study.A set of thematic data analysis was directed by the assistance of the NVIVO 8 Software.Finding identified that negotiation from the Islamic approach means a platform of arguments between two parties or more within the Shariah teachings to obtain spiritual satisfaction.